Y-Hf co-doped Al1.1CoCr0.8FeNi high-entropy alloy with excellent oxidation resistance and nanostructure stability at 1200°C. (October 2021) - Lu, Jie; Zhang, Han; Li, Ling; Huang, Aihui; Liu, Xuanzhen; Chen, Ying; Zhang, Xiancheng; Guo, Fangwei; Zhao, Xiaofeng
Abstract: A new type of Y-Hf co-doped Al1.1 CoCr0.8 FeNi high-entropy alloy (HEA) with a coherent nanostructure and its oxidation behavior at 1200°C are reported in this work. The nanostructure is highly stable and almost no phase coarsening can be observed in the HEA substrate during the prolonged oxidation. The Y-Hf co-doped Al1.1 CoCr0.8 FeNi HEA exhibits a very low oxidation rate, which is even lower than that of the typical FeCrAlYHf alloy, while its resistance to scale spallation significantly outperforms the typical NiCoCrAlYHf alloy. The highly stable nanostructure is beneficial to increase the homogeneity of Y and Hf distribution and thus strengthens the reactive elements effect, which can lower the oxidation rate and the growth stress of Al2 O3 scale. Generally, the structural stability, the low growth rate of scale and the low growth stress of scale contribute to the excellent oxidation performance of Y-Hf co-doped Al1.1 CoCr0.8 FeNi HEA at 1200°C. Graphical abstract: Image, graphical abstract